Prayer for Family and Friends: The Body and Religion in Eighteenth-Century Britain - Harvey, Karen (The historical journal, 2024)
This article explores how writers, predominantly adhering to a variety of different Christian denominations but also including Jewish writers, discussed religion and the body in letters throughout the long eighteenth century. It draws on a corpus of over 2,500 familiar letters written by men and women of different denominations between 1675 and 1820. That these letters were not chosen because of their religious content makes them a good ‘test’ of the role of faith in everyday understandings of the body. This article underscores the continued centrality of religious discourse and devotional practice in eighteenth-century everyday life. Our research finds that religion was a commonplace register deployed when discussing bodily matters throughout the long eighteenth century. Significantly, this was the case for individuals who otherwise made scant reference to their faith. Discussion of the physical body encouraged recourse to providence, a public discussion of doctrine, and the shared expression of devotion. The ongoing force of religion in people’s lives was thus intimately tied to their embodied experiences. Letters not only expressed but actively maintained this widely shared religious framework for understanding the body.